Efektifitas Pelayanan Publik Di Kantor Kelurahan Tongkeina - Oroh, Johns A. Ch; Rares, Joyce; Pesoth, Welly (JURNAL ILMIAH SOCIETY, 2016)
This research was conducted in order to find out the public service management and community respond applied by Tongkaina Political District Office Bunaken Sub-district Manado City. This descriptive research is only to explain the situation of public service management in Tongkaina Political District Office Bunaken Sub-district Manado City. This research used descriptive analysis, to draw conclusion by in depth interview with secondary information as supported data. Then, the data researched based on the existing concepts from library. The result showed that the public service in Tongkaina Political District Office Bunaken Sub-district Manado Citystill far from maximum satisfaction